Universal versus Targeted Preschools: An Optimal Tax Approach - Dominik Sachs; Brant Abbott (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Many governments set up large public preschool programs in order to expand ac- cess to early education (crowd-in). Public preschools, however, tend to crowd-out private preschool enrollment. This makes such programs less cost-effective because public finances are used to pay for preschool for children that would have been in (private) preschool oth- erwise. Making fees for public preschools increase with family income is a way to address this trade-off. Yet this creates adverse incentives for parental labor supply. Using methods of optimal nonlinear taxation, we derive a theory of income-contingent public preschool fees that optimally trade-off crowd-in, crowd-out and parental labor supply. The optimal shape of such a fee schedule depends on labor supply elasticities, crowd-in and crowd-out elasticities as well as on the progressivity of the pre-existing income tax schedule. The more progressive the income tax schedule is, the stronger are the adverse effects of a steep preschool fee schedule on labor supply. We calibrate our model to the U.S. and use in- formation on existing public preschool programs, enrollment rates and quasi-experimental evidence. We find that the government could increase overall preschool enrolment by 11 percentage points (19 percent) solely by targeting current subsidies more efficiently and without spending one single more dollar.
Keywords: H21; I20; J13; 330